GIS Developments for Ecosystem-based Marine Spatial Planning and the Challenges Faced in Indonesia - Karlina Triana; A'an Johan Wahyudi (Universitas Gadjah Mada, 2019)
Aiming to lessen degradations and effects on marine ecosystems, Marine Spatial Planning is used as a management method with a purpose to help lead the development and used in the marine environment. The stages of the planning are collection, management, and analysis of spatial data, and also decision support systems. This method requires tools to be able to achieve the goals effectively. Geographic Information System (GIS) and remote sensing can efficiently and effectively be used to access and summarize spatial data into information forms to evaluate the Marine Spatial Planning projects. GIS and remote sensing obviously have an essential function in terms of its opportunities and its capabilities for development and projections in the future. This review is intended to produce critical description on the study of GIS development for Marine Spatial Planning. Furthermore, this review is intended to foresee the challenges faced in its implementation in Indonesia.